Історичні дисципліни як складова вищої освіти в україні на початку ХХІ ст. - Мотенко, Ярослав Володимирович; Шишкіна, Євгенія Костянтинівна (Глухівський національний педагогічний університет ім. Олександра Довженка, 2018)
У статті запропоновано аналіз основних тенденцій розвитку історичної освіти як важливої складової навчально-виховного процесу у вищій школі України на початку ХХІ ст. Окреслено проблемні питання модернізації викладання історичних дисциплін на сучасному етапі. Окремо розглянуто особливості викладання «Історії України» у технічних вищих навчальних закладах.

The article offers an analysis of the main trends in the development of historical education as an important component of the educational process in the higher school of Ukraine at the beginning of the 21st century. The problematic issues of transformation in the sphere of teaching of historical disciplines at the present stage are determined. Separately, the specific characteristics of teaching «History of Ukraine» in technical universities are examined. The authors consider the modernization of learning process in the institutions of higher education of Ukraine as a dialectic issue containing certain risks for humanities’ component of bachelors’ and masters’ preparation. Important stages of this process were events of 2009, 2014 and 2015. They demonstrated the fundamental divergence of views on the ways of higher schools’ reforming in Ukraine of the most part of humanities’ academic community on the one hand, and state bureaucracy on the other. The public debate on the role of historical disciplines in the preparation of modern graduates of higher schools of Ukraine revealed a number of pedagogical, didactical and methodological problems. Among these the challenge of distinguishing between secondary and higher school courses of «History of Ukraine» was recognized. The subject of intense discussion is the mechanism for the enforcement of the problem and dialogical methods to the teaching process of the institutions of higher education. In the end, it was made the conclusion that the aspiration of the senior management of the Ministry of Education and Science of Ukraine to cut back as short as possible schedule of hours for humanities in the institutions of higher education (especially in the technical and military universities) can have serious social and political consequences. Ignoring the importance of the discipline «History of Ukraine» in developing of the technical students’ and cadets’ world view in the conditions of the «hybrid war» could become an essential precondition for losing the informational war by Ukraine. Authors bring to the attention that among the political elite of Ukraine dominate technocratic understanding of term «information security». As a result, historical disciplines are turning into outsiders of educational process thus making it more difficult to consolidate Ukrainian society in the period of the serious military-political crisis.
Historical disciplines as a part of higher education in Ukraine at the beginning of XXI century
Keywords: вища школа; історична освіта; модернізація; історія України; історія української культури; історія та культура України; higher school; historical education; modernization; history of Ukraine; history of Ukrainian culture; history and culture of Ukraine